ONLINE STATIONERY ORDERING SYSTEM - Soon, Hii Lu (Universiti Teknologi Petronas, 2006)
This paper contributes a research on rule based online stationery ordering system in UTP. The system is rule based system because the lecturers must obtain approval from 2 layers of top management before passing the application to stationery unit for further processing. The objective of the system development is trying to automate the ordering. The innovation started when the current manual system is giving lot of weakness to the users in UTP. It is time consuming for user especially the lecturers to request for stationery . Sometime they may have to wait almost nine month to get the stationery. This cause some lecturer prefer purchase themselves at supermarket rather than go through such complicated procedures. The system is running on intranet and only accessible within network UTP. The system will connect all client pc from lecture, Program Head and Head HRM to the server which install at stationery unit. The stationery unit also works as administrator to control and maintain the system. The system will apply the use of Rapid Application Development (RAD) as the methodology to the system development. The RAD been chosen since it easy to apply and produce low failure to the system compare to other model. Research has done to the some ordering system in website which applied the use of rule bases system as well. An online survey has been done to the UTP lecturers and the staff in Stationery Unit to get their suggestion on the idea of the Online Stationery Ordering System (OSOS). The development of the current OSOS is base to the lecturers' requirement.